Debt Sustainability, Public Investment, and Natural Resources in Developing Countries : the DIGNAR Model - Melina, Giovanni (IMF Working Papers; Working Paper ;, 2014)
This paper presents the DIGNAR (Debt, Investment, Growth, and Natural Resources) model, which can be used to analyze the debt sustainability and macroeconomic effects of public investment plans in resource-abundant developing countries. DIGNAR is a dynamic, stochastic model of a small open economy. It has two types of households, including poor households with no access to financial markets, and features traded and nontraded sectors as well as a natural resource sector. Public capital enters production technologies, while public investment is subject to inefficiencies and absorptive capacity constraints. The government has access to different types of debt (concessional, domestic and external commercial) and a resource fund, which can be used to finance public investment plans. The resource fund can also serve as a buffer to absorb fiscal balances for given projections of resource revenues and public investment plans. When the fund is drawn down to its minimal value, a combination of external and domestic borrowing can be used to cover the fiscal gap in the short to medium run. Fiscal adjustments through tax rates and government non-capital expenditures-which may be constrained by ceilings and floors, respectively-are then triggered to maintain debt sustainability. The paper illustrates how the model can be particularly useful to assess debt sustainability in countries that borrow against future resource revenues to scale up public investment.